France : Financial Sector Assessment Program-Technical Note-Key Attributes of Effective Resolution Regimes for Insurance Companies. (IMF Staff Country Reports; Country Report, 2019)
This technical note explores key attributes of effective resolution regimes (KA) for insurance companies on France. The safety net in the sector is composed by two policyholder protection schemes, which can provide support in liquidation proceedings. The report highlights that there is consensus with the authorities that the new framework reflects many, however, not all elements needed for full compliance with the KAs, and the areas where further progress is needed. Alignment of the framework with KAs in terms of the institutional organization and infrastructure is high. The scope and responsibilities of the Prudential Supervision and Resolution Authority are clearly established in the law, as well as the cases when those are applicable, and its interaction with other relevant policy-making entities. The new framework targets all institutions considered systemic, given their size and other relevant features. Its' current implementation is guided solely by the threshold in terms of total assets; any holding company, group, mutual, or foreign subsidiary above this level is subject to Recovery and Resolution Planning requirements.